2014
DOI: 10.1002/path.4399
|View full text |Cite
|
Sign up to set email alerts
|

TheIL‐13/IL‐4Rαaxis is involved in tuberculosis‐associated pathology

Abstract: Human tuberculosis (TB) is a leading global health threat and still constitutes a major medical challenge. However, mechanisms governing tissue pathology during post-primary TB remain elusive, partly because genetically or immunologically tractable animal models are lacking. In human TB, the demonstration of a large relative increase in interleukin (IL)-4 and IL-13 expression, which correlates with lung damage, indicates that a subversive T helper (TH)2 component in the response to Mycobacterium tuberculosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 54 publications
5
71
0
Order By: Relevance
“…Our findings agree with previous observations showing increased Arg1 mRNA expression and Arg1 activity over the course of aerosol Mtb infection and its association with augmented bacterial burden in murine lungs (22,26,50). Using the aerosol Mtb challenge of macrophage Arg1-deficient mice, El Kasmi et al (22) demonstrated improved control of Mtb in the lung.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings agree with previous observations showing increased Arg1 mRNA expression and Arg1 activity over the course of aerosol Mtb infection and its association with augmented bacterial burden in murine lungs (22,26,50). Using the aerosol Mtb challenge of macrophage Arg1-deficient mice, El Kasmi et al (22) demonstrated improved control of Mtb in the lung.…”
Section: Discussionsupporting
confidence: 83%
“…Murine studies argue that Arg1 participates in dampening effective immunity against Mtb, because aerosol Mtb-infected mice that are deficient in macrophage-specific Arg1 have lower bacterial loads and smaller cellular infiltrates in the lungs than similarly infected WT mice (22). Moreover, Mtb aerosol infection of transgenic mice that overexpress IL-10 and IL-13 in macrophages results in increased pulmonary expression of Arg1, correlating with increased bacterial loads as compared with WT mice (25,26). In these mouse models, Arg1 expression was linked to reduced production of RNIs, suggesting that L-arginine depletion by Arg1 suppresses NOS2 activity and, therefore, Mtb killing (22,25).…”
mentioning
confidence: 99%
“…Further, in IL-4 + IL-10-polarized MFs, the use of L-citrulline as a source of L-arginine may bypass arginase-mediated inhibition of iNOS function and elicit better antimycobacterial immunity. This method of polarization is likely relevant in vivo, because M. tuberculosis-infected patients with elevated type 2 cytokines have increased prevalence of TB (27)(28)(29). To test this, PDMs were stimulated with IL-4 + IL-10 for 24 h prior to infection to further induce Arg1 activity.…”
Section: Synthesized L-arginine Enhances Mycobactericidal Mf Activitymentioning
confidence: 99%
“…Caseous necrosis and cavitation during infection by M. tuberculosis is more prominent in rabbits and guinea pigs than in mice (2). Nevertheless, human-like pathology, as central granuloma necrosis and associated hypoxia, can be obtained in M. tuberculosis-infected I/StSnEgYCit, C3HeB/ FeJ, or IL-13-overexpressing C57BL/6 mouse strains (3)(4)(5). Confluent necrotic granulomas also are observed in mice deficient in gamma interferon (IFN-␥) or the type 1 tumor necrosis factor (TNF) receptor (2,6,7).…”
mentioning
confidence: 99%